Adapting Copy-Paste Phenomenon Into a New Music l Menyadur Fenomena "Copy-Paste" ke dalam Musik Baru - I Wayan Dibya Adi Guna; Ni Wayan Masyuni Sujayanthi (GHURNITA: Jurnal Seni Karawitan, 2021)
As a director, the stylist captures an interesting phenomenon that is often done among students and students are choose something instant like Copas (copy paste). Moving on from this phenomenon, the organizers reviewed the bright side of copas to change one's mindset that copas not only copy and paste raw, but copas is a bright spot from the dead end of inspiration to find references as reference material to compose a work that suits the character of the tenant himself. This film aims to awaken people's love for karawitan art through innovative karawitan works. The stylists use the method of making "Panca Sthiti Ngawi Sani". The implementation of the stages of the method in the implementation of a work can bring out the characteristics of the work itself so as to give birth to a new musical work with its own originality. The work is realized into three parts, namely introduction, situation, and resolution. In this structure the shape of the directed will resemble the pyramid pattern which in the middle as the climax of this work. The result of this work is a work with the concept of copy paste for originality, whose context in music as a work that "roughly" copies a song form from the original instrument is pasted into a different instrument raw, which has the effect of causing differences in the color of the sound when listening to the instrument. It is hoped that this work can benefit young kaula and art connoisseurs.